2023
DOI: 10.1136/thorax-2023-220001
|View full text |Cite
|
Sign up to set email alerts
|

Invitation strategies and participation in a community-based lung cancer screening programme located in areas of high socioeconomic deprivation

Abstract: IntroductionAlthough lung cancer screening is being implemented in the UK, there is uncertainty about the optimal invitation strategy. Here, we report participation in a community screening programme following a population-based invitation approach, examine factors associated with participation, and compare outcomes with hypothetical targeted invitations.MethodsLetters were sent to all individuals (age 55–80) registered with a general practice (n=35 practices) in North and East Manchester, inviting ever-smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…There are three types of recruitments for screening: active, where a high-risk subject is identified with the goal to set a first appointment; voluntary, where the subject reaches out to the screening program autonomously; and GP based. An implementation to active recruitment can be found in the Targeted Lung Health Check (TLHC) program, where effective communication reduced the risk of community stigmatization and mobile scanners were used close to social facilities [60][61][62][63]. Regarding the SMAC-1 recruitment phase, 67% of eligible subjects joined the screening.…”
Section: Discussionmentioning
confidence: 99%
“…There are three types of recruitments for screening: active, where a high-risk subject is identified with the goal to set a first appointment; voluntary, where the subject reaches out to the screening program autonomously; and GP based. An implementation to active recruitment can be found in the Targeted Lung Health Check (TLHC) program, where effective communication reduced the risk of community stigmatization and mobile scanners were used close to social facilities [60][61][62][63]. Regarding the SMAC-1 recruitment phase, 67% of eligible subjects joined the screening.…”
Section: Discussionmentioning
confidence: 99%
“…A US study found that 54.5% of patients had implausible changes in their smoking status, such as current smoker to never smoker [ 64 ]. A recent large UK study found that individuals with missing smoking data in PCP were more likely to have a history of smoking [ 65 ]. Programmes that include PCP based eligibility criteria should consider ways to inform those recorded as non-smokers or those with missing records about the programme, and invite them to contact the programme via low cost mechanisms such as text messaging, electronic portal notification, or letters; notifying potentially eligible patients of the programme and smoking eligibility criteria, and that if they believe their data is incorrectly recorded or that they may be eligible (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Programmes that include PCP based eligibility criteria should consider ways to inform those recorded as non-smokers or those with missing records about the programme, and invite them to contact the programme via low cost mechanisms such as text messaging, electronic portal notification, or letters; notifying potentially eligible patients of the programme and smoking eligibility criteria, and that if they believe their data is incorrectly recorded or that they may be eligible (e.g. for lung cancer screening or AAA screening) [ 65 , 66 ]. Studies have observed the unreliability of self-reported smoking status and looked at ways to tackle the underestimation of true smoking using objective measurements of smoking exposure, such as measurements of blood or urinary biomarkers [ 23 , 67 71 ].…”
Section: Discussionmentioning
confidence: 99%